New information on the Hind limb feathering, soft tissues and skeleton of Microraptor (Theropoda: Dromaeosauridae) - Matthieu Chotard; Xiaoli Wang; Xiaoting Zheng; Thomas G. Kaye; Maxime Grosmougin; Luke Barlow; Martin Kundrát; T. Alexander Dececchi; Michael B. Habib; Juned Zariwala; Scott Hartman; Xing Xu; et al. (BMC Ecology and Evolution)
Abstract Background Microraptor is known as the most significant example of extended feathering on the legs of a paravian, both fossil and modern. Its striking difference with most paravians contributes to the multiple theories on the function of its conspicuous hind limbs. Recent studies tried to uncover its evolutionary significance, but its anatomy has only been described from a small number of samples. Results Through the analysis of 16 specimens of Microraptor, including 8 previously undescribed specimens, here we provide new information on the structure and number of hindwing feathers within a revised feather taxonomy, including a revised shape of the hindwing Microraptor which displays feathers all along the hind limb, except along its pedal digits. Here we describe in detail 6 feather types: metatarsal remiges, long metatarsal coverts, long femoral feathers as well as the first description of long tibial feathers, anterior coverts and minor coverts. Our study of specimens BMNHC PH881 and STM 5–5, 5–75, 6–62 and 6–86 is partially consistent with previous work, but the key difference in this study is a proximal shift of the triangular wing portion formed by the long tibial feathers and the long metatarsal coverts that outlines the joint between the tibiotarsus and metatarsus. This configuration does not exist in any extant or fossil bird, or in any other non-avian paravian described so far, underscoring the uniqueness of Microraptor. Unlike previous reconstructions, here the long metatarsal coverts display an asymmetrical close-vanned structure as in the metatarsal remiges. The feathers as preserved are posteriorly projected along the metatarsus and vary between medioposterior and lateroposterior projection along the tibial feathers. Conclusions The overall configuration of feather layers is only found in Microraptor, and the two layers of elongated and asymmetrically vaned feathers linked to the metatarsus are more reminiscent of the forewing of modern birds than of any leg in other fossils and modern taxa. These new observations allow us to better understand the flight, non-flight locomotion and hunting strategies of this iconic ‘four-winged’ dinosaur suggesting Microraptor had a complex behaviour that made it adapted to arboreal and terrestrial habitats.